2013
DOI: 10.3389/fpubh.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Awareness and Associated Factors among Older Chinese Adults

Abstract: Hypertension is one of the most preventable chronic conditions. Improving hypertension awareness is a critical first step to reducing morbidity and mortality from hypertension in the elderly, yet the factors associated with hypertension awareness in China are poorly understood. The objective of this paper is to examine the extent to which older Chinese adults are aware of their hypertension, and factors associated with this awareness. We included 2404 adults aged 60 years or older clinically identified as hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…In contrast to other studies 17 , 27 , health-related behavioral factors such as drinking and physical activities were not substantially associated with sensitivity for CVD risk factors. Only smoking influenced an awareness of CVD risk factors on health-related behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies 17 , 27 , health-related behavioral factors such as drinking and physical activities were not substantially associated with sensitivity for CVD risk factors. Only smoking influenced an awareness of CVD risk factors on health-related behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Reports from elsewhere have shown divergent results in this regard. Significant relationships were found in studies conducted in China and Hong Kong [22,31], but no significant relationship was found in Korea [22]. Differences in the proportions of false negatives and false positives in these studies may help explain the discrepancies in their results.…”
Section: Discussionmentioning
confidence: 95%
“…Second, awareness, treatment, and control of hypertension remained at unacceptably low levels. Screening and monitoring efforts should be strengthened to increase hypertension awareness among people at risk [26]. This is important because early diagnosis and treatment of hypertension rely heavily on increasing population awareness [27].…”
Section: Discussionmentioning
confidence: 99%